2019
DOI: 10.1017/s0033291719000370
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use disorders may protect against certain disorders of the digestive organs in people with schizophrenia but not in healthy controls

Abstract: Background. Previous studies have shown a potential for cannabis in disorders of the digestive organs. We aimed to investigate whether cannabis use disorders (CUD) would decrease the risk of incident disorders of the digestive organs, in people with schizophrenia and population controls.Methods. We combined nationwide Danish registers to identify 21 066 cases with schizophrenia and 176 935 sex-and-age-matched controls. Two models were analyzed for the associations between CUD and digestive disorders in time-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This effect may be more pronounced if it is also accompanied by mild increase in the levels of the anti-inflammatory regulators IL-1RA and sTNFR1. Supportive of this idea, a recent report revealed that Cannabis use disorder is associated with decreased risk of diseases of gut-brain interaction and inflammatory bowel disease in SCZ, but not in healthy controls (36). Since circulating inflammatory biomarker levels are inversely correlated with negative symptom severity in SCZ (11,12), the documented anti-inflammatory effect of Cannabis may stand in the background of the observed associations between Cannabis consumption and improved mood regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be more pronounced if it is also accompanied by mild increase in the levels of the anti-inflammatory regulators IL-1RA and sTNFR1. Supportive of this idea, a recent report revealed that Cannabis use disorder is associated with decreased risk of diseases of gut-brain interaction and inflammatory bowel disease in SCZ, but not in healthy controls (36). Since circulating inflammatory biomarker levels are inversely correlated with negative symptom severity in SCZ (11,12), the documented anti-inflammatory effect of Cannabis may stand in the background of the observed associations between Cannabis consumption and improved mood regulation.…”
Section: Discussionmentioning
confidence: 99%